A real-world retrospective study to assess efficacy and safety of alectinib as adjuvant therapy in IB-IIIB NSCLC patients harboring ALK rearrangement - Chang, Zeng-Hao; Zhu, Teng-Fei; Ou, Wei; Jiang, Hao; Wang, Si-Yu (Frontiers in Oncology, 2024)
BackgroundAlectinib has demonstrated promising disease-free survival (DFS) benefit for early-stage non-small cell lung cancer (NSCLC) patients with ALK rearrangement positive in phase 3 ALINA trial. However, real-world evidence for the efficacy and safety of alectinib in early-stage ALK-positive NSCLC is limited.Materials and methodsWe retrospectively reviewed 68 patients with stage IB-IIIB ALK-positive NSCLC who underwent complete pulmonary resections from April 2010 to July 2023 at a single institution. 38 (55.9%) enrolled patients had N2 lymph node metastasis, and 17 (24.9%) patients had multi-station N2 metastasis. Patients were stratified into two groups according to the adjuvant treatment regimen, with 19 patients in the alectinib group and 49 patients in the chemotherapy group. There were no significant differences in clinicopathological characteristics between the two groups. After curative resection surgery, patients in alectinib group received oral alectinib at a dose of 600 mg twice daily and patients in chemotherapy group received platinum-based doublet chemotherapy regimen every 3 weeks for 4 cycles. The primary endpoint was 3-year DFS. The Kaplan-Meier method was used to estimate DFS and overall survival (OS). Safety analyses were conducted by comparing the incidence of adverse events between the two groups.ResultsAt the last follow-up date (January 22th, 2024), A total of 1 (5.3%) and 28 (57.1%) DFS events were observed in alectinib group and chemotherapy group respectively. The 3-year DFS showed significant improvement in the alectinib group compared with chemotherapy group (91.7% vs 60.7%, P=0.051). In the IIIAN2 subgroup, the 3-year DFS rate in the alectinib group reached a satisfactory 87.5%. In both groups, the majority of AEs were graded as level 1 or 2, No grade 3-4 AEs were observed in alectinib group.ConclusionAlectinib, as adjuvant therapy, demonstrated favorable efficacy and manageable safety in patients with completely resected ALK-positive stage I B-IIIB non-small cell lung cancer. A limitation of this study is the small sample size, and a larger-scale real-world sample study is needed to further evaluate the efficacy and safety of alectinib as adjuvant therapy.